THE RELATIONSHIP BETWEEN ISLAMIC TEACHINGS AND CULTURAL VALUES IN SHAPING ATTITUDES TOWARDS GENDER ROLES IN INDONESIA - Bouchouk, Oumaina; Ayaz, Maria (REVIEW OF MULTIDISCIPLINARY EDUCATION, CULTURE AND PEDAGOGY, 2024)
The relationship between Islam, culture, and attitudes towards gender roles in Indonesian society is a complex and dynamic phenomenon that requires a nuanced and interdisciplinary approach to be fully understood. This study aims to explore the interplay between Islamic teachings, cultural values, and attitudes towards gender roles in Indonesia through an interpretive case study. Semi-structured interviews were conducted with a purposive sample of 20 participants, including religious leaders, scholars, activists, and members of the general public. Documentary sources such as religious texts, academic journals, and news articles were also analyzed. The collected data was analyzed using a thematic analysis approach, and the findings were synthesized and interpreted to provide answers to the research questions. The study reveals that the relationship between Islamic teachings, cultural values, and attitudes towards gender roles in Indonesia is complex and multifaceted. Islamic teachings emphasize modesty, respect for elders, and traditional gender roles, significantly shaping attitudes towards gender equality and women's roles in society. However, local cultural beliefs and practices with strong patriarchal underpinnings also reinforce gender inequalities. This dynamic interplay between Islam and culture requires a nuanced and interdisciplinary approach to be fully understood. The study underscores the importance of understanding how religion, culture, and gender roles shape societal attitudes and values. It also highlights the need for further research to deepen the understanding of Indonesia's social, cultural, and religious dynamics and their impact on women's positions in society.